Relationship of Age, Parity, and History of Abortion With the Incidence of Incomplete Abortion at RSUD Dr. HM Rabain Muara Enim 2021 - Eva Kurnia; Siti Aisyah; Erma Puspitasari (Science Midwifery, 2022)
Incomplete abortion is the expulsion of the products of conception that occurs at 20 weeks of gestation and the fetus weighs 500 grams and there are remnants left in the uterus. This study aims to determine the relationship between age, parity and history of abortion simultaneously with the incidence of incomplete abortion in RSUD Dr.HM Rabain Muara Enim 2021. The method used in this study is a quantitative study with an analytical survey method with a cross sectional approach. The population in this study were all mothers who were treated in the Midwifery Care Room without giving birth as many as 523 people, with a total sample of 84 people. The sampling technique in this study was Systematic random sampling with class intervals. The statistical test used is the chi square test. Through the analysis, the results obtained from 33 respondents of high risk age who experienced incomplete abortion as many as 25 respondents (75.8%) and 8 respondents (24.2%) who did not experience incomplete abortion, where p value 0.007 and OR 4.119 means that there is a relationship between age mothers with incomplete abortions. Of the 40 respondents with high parity, 26 respondents (65%) experienced an incomplete abortion and 14 respondents (35%) did not experience an incomplete abortion with ap value of 0.170 and an OR of 2.034, which means that there is no parity relationship with the incidence of incomplete abortion. abortion. and of the 21 respondents who had a history of abortion, there were 18 respondents (85.7%) who had incomplete abortions and 3 respondents (14.3%) did not experience an incomplete abortion with ap value of 0.004 OR 7.034, meaning that there was a relationship between the history of abortion and the incidence of abortion. . Incomplete. The results of this study are expected to be input for improving the quality of services for pregnant women so as to reduce the incidence and mortality due to incomplete abortion.